The Effectiveness of Integrated Augmented Reality Media With Lamongan Local Culture to Overcome Difficulties in Understanding Pancasila in The Second and Fifth Principles in Elementary School Students - Riska Dwi Berilana Pasiyantiningsih; Maretha Dellarosa; Ari Metalin Ika Puspita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Difficulties in understanding the values of Pancasila persist among elementary school students, especially in the second and fifth precepts, which contain abstract concepts of humanity and social justice. Learning that is still dominated by conventional methods makes it difficult for students to connect the material to real-life experiences. This study aims to analyze the effectiveness of Augmented Reality (AR) media integrated with Lamongan local culture in overcoming difficulties in understanding Pancasila in the second and fifth precepts in elementary school students. The research uses a quantitative approach with a quasi-experimental pretest-posttest control-group design. The research subjects were 64 elementary school students, divided into two groups: 32 in the experimental group and 32 in the control group. The experimental group obtained learning using AR media integrated with Lamongan local culture, while the control group used conventional learning media. Data collection was carried out through Pancasila understanding tests, observation sheets, and student response questionnaires. Data analysis used the N-Gain test, the independent-samples t-test, and effect size to determine the level of media effectiveness. The study's results show that integrating AR media with Lamongan local culture significantly increases students' understanding compared to conventional learning. The experimental group's posttest score was higher than the control group's, with moderate to substantial improvement in N-Gain results. The three-dimensional visualization and interactivity displayed through AR technology help students understand the meaning of just and civilized human values and social justice for all Indonesian people in a more concrete way. In addition, integrating Lamongan's local culture provides a learning context close to students' lives, thereby increasing engagement, motivation, and meaningful learning experiences. Thus, Lamongan's locally integrated AR media has proven effective in overcoming difficulties in understanding the second and fifth precepts of Pancasila among elementary school students and has the potential to become an innovation in Pancasila Education that is relevant to the demands of 21st-century education.